Equivocal Effect of Intraoperative Fluorescence Angiography on Colorectal Anastomotic Leaks. Issue 6 (June 2015) - Kin, Cindy; Vo, Hong; Welton, Lindsay; Welton, Mark
Abstract : BACKGROUND: Intraoperative fluorescence angiography is beneficial in several surgical settings to assess tissue perfusion. It is also used to assess bowel perfusion, but its role in improving outcomes in colorectal surgery has not been studied. OBJECTIVE: The purpose of this work was to determine whether intraoperative angiography decreases colorectal anastomotic leaks. DESIGN: This was a case-matched retrospective study in which patients were matched 1:1 with respect to sex, age, level of anastomosis, presence of a diverting loop ileostomy, and preoperative pelvic radiation therapy. SETTINGS: The study was conducted at an academic medical center. PATIENTS: Patients who underwent colectomy or proctectomy with primary anastomoses were included. INTERVENTIONS: The intraoperative use of fluorescence angiography to assess perfusion of the colon for anastomosis was studied. MAIN OUTCOME MEASURES: Anastomotic leak within 60 days and whether angiography changed surgical management were the main outcomes measured. RESULTS: Case matching produced 173 pairs. The groups were also comparable with respect to BMI, smoking status, diabetes mellitus, surgical indications, and type of resection. In patients who had intraoperative angiography, 7.5% developed anastomotic leak, whereas 6.4% of those without angiography did ( p value not significant). Univariate analysis revealed that preoperative pelvic radiation, more distal anastomosis, surgeon, and diverting loop ileostomy were positively associated with anastomotic leak. Multivariate analysis demonstrated that level of anastomosis and surgeon were associated with leaks. Poor perfusion of the proximal colon seen on angiography led to additional colon resection before anastomosis in 5% of patients who underwent intraoperative angiography. LIMITATIONS: The retrospective study design with the use of historical control subjects, selection bias, and small sample size were limitations to this study. CONCLUSIONS: Intraoperative fluorescence angiography to assess the perfusion of the colon conduit for anastomosis was not associated with colorectal anastomotic leak. Perfusion is but one of multiple factors contributing to anastomotic leaks. Additional studies are necessary to determine whether this technology is beneficial for colorectal surgery.